Inventory, Prevalence and Intensity of Ectoparasites at Groupers (Epinephelus sp.) in Floating Nets Hurun Bay Lampung - Sumino Sumino; Cicilia Tri Anggraeni; Tardiono Tardiono (Jurnal Perikanan dan Kelautan, 2017)
he limiting factor in aquaculture is disease. Ectoparasites is one of the disease ingrouper (Epinephelus sp.) cultivated using floating nets. In Hurun Bay Lampung, thereare many grouper cultivation using  floating nets. This study aims to inventory the typesof ectoparasites that infect grouper, to determine the prevalence and intensity ofectoparasites. Sampling of grouper was done on March 30th to 31st and September 29Inventarisasi, prevalensi dan intensitas ektoparasit …..                                                                       1 th to30th 2016 in floating nets owned by Mr. Untung and Mr. Asril in Hurun Bay Lampung.Random samples were taken with 25 fishes for each Grouper population. Identification ofectoparasites was conducted in the laboratory of FQIA Regional Lampung throughmorphological observation using a microscope. Three types of ectoparasites that wereidentified are Pseudorhabdosynochus sp., Haliotrema sp. and Benedenia sp. The range ofprevalence and intensity of Pseudorhabdosynochus sp., Haliotrema sp., and Benedenia sp. is respectively 0-32% (from 0 to 7.6 individu/fish), 0-28% (0-5 individu/fish), and12% (0 to 3.33 individu/fish).